Left ventricular ejection power in coronary artery disease during atrial pacing. Issue 2 (February 1979) - Hagemann, K; Meyer, J; von Essen, R; Krebs, W; Effert, S
Abstract : Peak and mean left ventricular ejection power were measured during atrial pacing in 6 normal subjects (group I), 6 patients with coronary artery disease without myocardial infarction (group IIa), and 10 patients with coronary artery disease after myocardial infarction (group IIb). Pacing rates were 80 and 120/min. Power was determined by computer analysis of pressure, volume, and time. Data were normalised by end-diastolic volume and left ventricular muscle mass. Peak left ventricular ejection power normalised by end-diastolic volume values at a pacing rate of 120 min were significantly lower in group IIa and IIb than in normal subjects. Mean muscle mass in normal subjects was 179 g and in group IIa 216 g (P smaller than 0.05). Peak power normalised by muscle mass in normal subjects tended to increase at 120/min whereas in group IIa it declined by 26 per cent (P less than 0.001). These data indicate that the energy output of the left ventricle at rest may be the same in patients with significant coronary artery disease as in normal subjects. Increasing the heart rate from 80 to 120/min in a normal myocardium augments power but in coronary artery disease it remains static or falls.